Penerapan Pembuatan Biodata Mahasiswa Perguruan Tinggi Bina Sriwijaya Menggunakan Microsoft Visual Basic 6.0: Penerapan Pembuatan Biodata Mahasiswa Perguruan Tinggi Bina Sriwijaya Menggunakan Microsoft Visual Basic 6.0 - AKHMAD SAYUTI; Zet Abdullah; Irian Nasri; Januar Ida Wibowati (S1 Teknik Mesin Fakultas Teknik. Universitas Negeri Surabaya Gedung A6 Kampus UNESA Ketintang Surabaya 60231, 2025)
The development of information technology provides convenience in data management, including in the world of higher education. Bina Sriwijaya College requires an efficient and computerized system to manage student biodata data precisely and accurately. This study aims to design and implement a student biodata processing application using Microsoft Visual Basic 6.0 as the main programming language. The system development method used is waterfall, starting from needs analysis, design, implementation, to system testing. The result of this study is an application that is able to store, display, change, and delete student biodata data with a simple and easy-to-use interface. With this system, the process of managing student data becomes more efficient, reduces manual recording errors, and makes it easier to search and report data.